The levels of forming richly oriented mobility at students of general school as analytical and programming part of free behavior management and moving activity. - Artyushenko А.О (Kharkov National Pedagogical University, 2011)
The aim of a research is to study indexes of forming at students of general school. It was singled out four levels. It was show that for the period of study at school the level of forming richly oriented mobility from junior till elder children do not have some changes. So educational athletic activity have no influence on students' indexes of forming richly oriented mobility.